2015
DOI: 10.1016/j.healthplace.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Cycling for transport and recreation: Associations with the socio-economic, natural and built environment

Abstract: This study examined associations between objective environmental attributes and, separately, transport (TC) and recreational cycling (RC). Environmental attributes were more strongly associated with TC than RC. Distances to areas with the best bicycle infrastructure and urban amenities may be key environmental attributes influencing TC but not RC. Government investments in bicycle infrastructure within inner Brisbane appear to have resulted in more TC than in outer areas and to appeal to residents of both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
57
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 40 publications
5
57
2
1
Order By: Relevance
“…We focus our review on studies of utilitarian cycling (i.e. cycling for transportation, including commuting), as past research has demonstrated that utilitarian and recreational cycling are characterized by different patterns of behavior (Heesch et al, 2015;Heinen et al, 2010;Hoehner et al, 2005;Vernez-Moudon et al, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…We focus our review on studies of utilitarian cycling (i.e. cycling for transportation, including commuting), as past research has demonstrated that utilitarian and recreational cycling are characterized by different patterns of behavior (Heesch et al, 2015;Heinen et al, 2010;Hoehner et al, 2005;Vernez-Moudon et al, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research exploring the influence of the environment on physical activity has emerged in the past decade 6–10 . Environmental factors explored include: the built environment, such as proximity to parks, playgrounds and sports facilities; access characteristics, such as transport, footpaths, traffic lights and crossings; the natural environment such as climate and weather; and perceptions of safety 6,7 .…”
mentioning
confidence: 99%
“…A review of environmental characteristics relevant to young people's use of sports facilities found consistent and positive associations between physical activity and the presence of sport facilities, open parks and play‐recreational facilities 6 . However, these findings were often limited to individuals’ perceptions of the environment, with few studies using objective measures 8–10 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the studies that only examined walking for transport, 13 out of 28 studies were of strong quality. For the studies that only studied cycling for transport, only one [59] out of ten studies was of strong quality. Regarding the studies that examined general AT, five out of six were of strong quality.…”
Section: Results Of Quality Assessmentmentioning
confidence: 99%